A Zbtb7a proto‐oncogene as a novel target for miR‐125a. Issue 12 (29th December 2015) - Hojo, Nozomi; Tatsumi, Naoya; Moriguchi, Nahoko; Matsumura, Akihide; Morimoto, Soyoko; Nakata, Jun; Fujiki, Fumihiro; Nishida, Sumiyuki; Nakajima, Hiroko; Tsuboi, Akihiro; Oka, Yoshihiro; Hosen, Naoki; et al.
Abstract : In our previous study, we showed that miR‐125a directly targeted a WT1 oncogene, which was overexpressed in leukemia and various kinds of solid tumors including lung, breast, gastric, and colon cancers, and brain tumors and was deeply involved in leukemogenesis and tumorigenesis and that miR‐125a knockout mice overexpressed WT1 and developed myeloproliferative disease. It had been also reported that miR‐125a is downregulated in leukemia and various types of solid tumors such as lung cancers, suggesting its tumor suppressor function. Therefore, it is important to elucidate what is target(s) of miR‐125a for understandings of such functions although few target genes for it are known. In the present study, Zbtb7a oncogene was identified as a potential target for miR‐125a by gene expression profiling in miR‐125a knockout mice combined with bioinformatics target prediction. EGFP‐3′UTR reporter assay showed that miR‐125a suppressed Zbtb7a expression through its direct binding to the Zbtb7a‐3′UTR. Zbtb7a knockdown by siRNA suppressed cell proliferation and induced G1 cell cycle arrest and apoptosis in lung cancer cells. Furthermore, miR‐125a expression showed a negative correlation with Zbtb7a expression in non‐small cell lung cancer tissues. The present study showed for the first time that Zbtb7a was a direct target for miR‐125a and was involved in cell cycle progression and apoptosis of lung cancer cells. These results also demonstrated that deregulation of miR‐125a‐Zbtb7a signaling was associated with the development and progression of lung cancer. © 2015 Wiley Periodicals, Inc.